The Effect of Instagram on Language Use and Culture in Millineals and Generation Z - Siti Azizah Puteri (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2022)
This study aims to examine the impact of Instagram on the linguistic and cultural communication patterns of Generation Z and Millennials. Employing a qualitative approach, the researcher collected data to address three distinct research questions: 1. How is Instagram utilized by these demographic groups? 2. What are the underlying factors that influence language and cultural usage on Instagram? 3. What specific linguistic styles are prevalent in their Instagram posts? The data collection process involved administering closed-ended questions to participants and conducting a rigorous analysis of the linguistic styles employed in their Instagram posts. Additionally, upon completion of the investigative procedures, the researcher will elucidate the underlying motivations and rationales behind the utilization of language and cultural elements in Instagram posts. Finally, the study incorporates a comprehensive review of relevant literature to supplement the findings and ensure a thorough examination of the research topic